Giovanni Paolo Lomazzo's Trattato dell'arte della pittura : color, perspective and anatomy - Tramelli, Barbara (Nuncius series., 2017)
Barbara Tramelli's Giovanni Paolo Lomazzo's Trattato dell'Arte della Pittura: Color, Perspective and Anatomy investigates the context in which the writings of the painter Giovanni Lomazzo were produced, the types of theoretical and practical knowledge which they conveyed to artists and how painters in the second half of the sixteenth century shared this knowledge among themselves. In his books, Lomazzo drew on earlier and contemporary art literature, his own expertise as a painter, works of natural philosophy and his personal exchanges with contemporary artists, astrologers and 'scientists'. Lomazzo and his work are placed in the context of the city where he operated and published, paying particular attention to the role of Milanese institutions as 'spaces of interactions' with colleagues and men of letters in which the material for his books was discussed and collected. Tramelli highlights three main areas of Lomazzo's studies: color, perspective and anatomy, linking his theoretical discourse to what was known and discussed about these topics in Milan at the end of the sixteenth century.